Novos olhares em torno da prática psicológica: o ponto de vista de profissionais que compõem as equipes multiprofissonais dos centros de atenção psicossocial - Cantele, Juliana (2013)
The rouse of the mental health workers launches the Brazilian Psychiatric Reform, aiming to overcome the model of health care centered in the hospital, leading the suffering subject to a more humanitarian form of treatment. Thus, the Psychosocial Health Centers enter into force to restore the bonds among the user, his/her familiy and society, broadening the possibilities of user embracement and care. The psychologist, together with other professionals, is inserted in such new model. This study aimed to know the interventions practiced by psychology, from the perspective of the multiprofessional team of two Psychosocial Health Centers of a medium-sized city in the interior of Rio Grande do Sul. A qualitative study was carried out, using semi-directed interviews, together with systematic observations in the two Psychosocial Health Centers. Content analysis, more specifically thematic content analysis was used to analyze data. Results are presented in two articles. The first one is entitled Resignifying Psychological Practice: the perspective of the multiprofessional team of Psychosocial Health Centers and approaches themes regarding the psychological practice in the perspective of professionals who took part in the study. Psychological practice was highlighted as relevant to assistance, being constituted of actions that include, besides the individual assistance activities, group, collective and interdisciplinary activities. The psychologist was identified as an integrating and participatory professional in the service, and pointed out as the professional who mediates the link among health professionals team-family-society. Psychological understanding was mentioned as differentiated from the other modalities of understanding, being the main tool used by the psychologist in such professional context. The second article, entitled The Multiprofessional Team and the interdisciplinary practice: challenges of the new health care model in Mental Health portrays themes concerning the multiprofessional work in an interdisciplinary and transdisciplinary perspective. Initially, the professionals pointed out the unpreparedness and the difficulties lived when the professionals began their activities in a PHC. Regarding such aspect, they refer the clinical and institutional supervision as one of the devices that helps overcoming the fragilities faced daily. The professionals emphasized the importance of the integration of professionals that are part of the multiprofessional teams, of the health care team meetings, and, at the same time, they mentioned the importance of the specificity of each professional nucleus, as regards the construction of a wider perspective in relation to the phenomena. Final considerations emphasize a significant movement of the psychological practice, evidenced by the overcoming of the basic individual model, that has marked the path of the professional practice. The resignification of the psychologist s practice in the daily work of institutions was identified, redefining his/her place within the mental health teams. In conclusion, the results convey that the psychology professional was not the only one who needed to resignify his/her practice. The other members of the multiprofessional team also needed to reorganize their functions regarding such new modality of mental health care that emerges from the emergence of PHC. Therefore, a movement in the direction of a more integrated practice, including interdisciplinary actions and supported by an interdisciplinary perspective, is evidenced.